2008
DOI: 10.1007/s00056-008-0803-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Condylar Differences in Functional Unilateral Posterior Crossbite during Early Treatment – a Randomized Clinical Study

Abstract: The Münster concept for early treatment of functional unilateral posterior crossbites in late deciduous and early mixed dentition significantly improved the treated patients' occlusion in comparison to a randomized control group, which exhibited no spontaneous self-healing tendencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…After correction of the maxillary discrepancy, an orthodontic activator treatment (U-Bow activator Type 1) as described by Karwetzky [12] was applied to achieve midline coordination and to retain the amount of palatal expansion (Figure 2b). Details are given by Lippold et al [7]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After correction of the maxillary discrepancy, an orthodontic activator treatment (U-Bow activator Type 1) as described by Karwetzky [12] was applied to achieve midline coordination and to retain the amount of palatal expansion (Figure 2b). Details are given by Lippold et al [7]. …”
Section: Methodsmentioning
confidence: 99%
“…In our own recent study [7], we established that therapeutic improvements in mandibular condyle position could be achieved using orthodontic treatment for functional unilateral posterior cross bite in a sample consisting of 65 children (6.9 ± 2.0 years of age) with late deciduous and early mixed dentition. Of the 65 children used in this randomized clinical trial, 31 underwent early orthodontic treatment and 34 did not.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it has been suggested that the altered morphological relationship between the upper and lower dentition may result in right-to-left-side differences in the condyle-fossa relationship, and in the height of the condyle and the mandibular ramus resulting in an asymmetric mandibular growth (41)(42)(43)(44)(45)(46). However, early treatment to normalize the occlusion created appropriate conditions to obtain a normal growing pattern both in animal studies and in human studies (44)(45)(46). Secondly, jaw function alteration including asymmetric pattern of jaw muscles EMG activity (47), lower bite forces (48), reduced thickness of the ipsilateral masseter (49) and a reverse sequence chewing pattern (50, 51) have been reported.…”
Section: Does Malocclusion Cause Tmd?mentioning
confidence: 99%
“…Of these, one study was eliminated because it was a protocol proposal to be followed in future studies, 15 one for evaluating pre-and post-intervention changes through gypsum models and bite registration, 16 one for assessing condylar change by means of zonograms, 17 and five studies were excluded since they examined patients who underwent slow maxillary expansion. 10,[18][19][20][21] Therefore, seven articles from the systematic search were included for qualitative analysis; [22][23][24][25][26][27][28] as well as one record found by hand search (n ¼ 1); 29 totaling eight articles included in this review ( Table 1). A quantitative analysis was not feasible given the heterogeneity in the methodology of the selected articles.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%